Direct observation of vast off-stoichiometric defects in single crystalline SnSe. (May 2017) - Wu, Di; Wu, Lijun; He, Dongsheng; Zhao, Li-Dong; Li, Wei; Wu, Minghui; Jin, Min; Xu, Jingtao; Jiang, Jun; Huang, Li; Zhu, Yimei; Kanatzidis, Mercouri G.; et al.
Abstract: Single crystalline tin selenide (SnSe) recently emerged as a very promising thermoelectric material for waste heat harvesting and thermoelectric cooling, due to its record high figure of merit ZT in mediate temperature range. The most striking feature of SnSe lies in its extremely low lattice thermal conductivity as ascribed to the anisotropic and highly distorted Sn-Se bonds as well as the giant bond anharmonicity by previous studies, yet no theoretical models so far can give a quantitative explanation to such low a lattice thermal conductivity. In this work, we presented direct observation of an astonishingly vast number of off-stoichiometric Sn vacancies and Se interstitials, using sophisticated aberration corrected scanning transmission electron microscope; and credited the previously reported ultralow thermal conductivity of the SnSe single crystalline samples partly to their off-stoichiometric feature. To further validate the conclusion, we also synthesized stoichiometric SnSe single crystalline samples, and illustrated that the lattice thermal conductivity is deed much higher as compared with the off-stoichiometric single crystals. The scattering efficiency of individual point defect on heat-carrying phonons was then discussed in the state-of-art Debye-Callaway model. Graphical abstract: Highlights: We directly observed a large number of off-stoichiometric point defects in single crystalline SnSe. Our findings help to understand why theoretical simulations show higher thermal conductivities than experimental ones. We present a quantitative explanation of the experimentally observed ultralow thermal conductivity in SnSe single crystals.